THE IMPROVED SOURCE CODE OF 3DINVERT.M MATLAB PROGRAM TO COMPUTED DENSITY TOPOGRAPHY OF GRAVITY ANOMALY REGIONAL OF BANTEN, INDONESIA BASED ON THE FAST FOURIER TRANSFORM - AYU ESTY WINDHARI (NIM:20210309); Pembimbing : Gunawan Handayani Ph.D., GUSTI
The 3D inversion gravity anomaly to estimated topography density using a matlab source code from gridded data by Parker Oldenburg algorithm based on fast Fourier transform was computed. We extended and improved source code of 3DINVERT.M by Gomez Ortiz and Agarwal (2005) that using the relationship between Fourier transform of the gravity anomaly and the sum of the Fourier transform of topography density. To apply we given density contrast between the two media. FFT routine was implemented to construct amplitude spectrum to given mean depth. The results were presented as new graphics of inverted topography density, the gravity anomaly due to the inverted topography and the difference between the input gravity data and the computed ones. It terminates when the RMS error is lower than pre-assigned value used as convergence criterion or until maximum of iterations is reached. As an example, we used the Matlab program on gravity data of Banten region, Indonesia.